2012
DOI: 10.1099/jmm.0.047514-0
|View full text |Cite
|
Sign up to set email alerts
|

Akwaton, polyhexamethylene-guanidine hydrochloride-based sporicidal disinfectant: a novel tool to fight bacterial spores and nosocomial infections

Abstract: Bacterial spores are of continuing interest to the food and medical industries. In efforts to eliminate bacterial spore contamination, a number of sporicidal agents have been developed. Most of these compounds must be used carefully in very specific circumstances as they are toxic to humans. The sporicidal activity of Akwaton, a polyhexamethylene-guanidine hydrochloride (PHMGH)-based disinfectant, was tested against Bacillus subtilis spores. PHMGH is a colourless, odourless, non-corrosive and non-irritating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 34 publications
(41 reference statements)
0
50
0
1
Order By: Relevance
“…Oulé et al [19] have clearly demonstrated its bactericidal activity against Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella choleraesuis, meticillin-resistant S. aureus (MRSA) and E. coli; its sporicidal activity against Bacillus subtilis spores [20] and its fungicidal activity against Trichophyton mentagrophytes [4]. In addition to its microbicidal properties, it has been demonstrated that AKWATON was much less toxic to rat cells than well-known disinfectants currently on the market.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Oulé et al [19] have clearly demonstrated its bactericidal activity against Staphylococcus aureus, Pseudomonas aeruginosa, Salmonella choleraesuis, meticillin-resistant S. aureus (MRSA) and E. coli; its sporicidal activity against Bacillus subtilis spores [20] and its fungicidal activity against Trichophyton mentagrophytes [4]. In addition to its microbicidal properties, it has been demonstrated that AKWATON was much less toxic to rat cells than well-known disinfectants currently on the market.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cell cultures and the different tests carried out by Oulé et al [20], showed that the new AKWATON-based disinfectant killed fewer animal cells than the commercial disinfectants, sparing 80% of rat pancreatic (C2C12) cells and 65% of muscle RnM5F cells, whilst some of the well-known disinfectants currently on the market killed 85-100% of those cells.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations